STYLISTIC CHARACTERISTICS AND DESCRIPTION OF ARTISTIC COMPOSITION BLOUSES 1950-1960-S - Головчанська, Є. О. (Art and Design, 2019)
Explore the characteristic artistic and compositional features of women’s blouses from the 1950s and 1960s, to identify and systematize the main tendencies in the development of forms, silhouettes and women’s blouses, to develop a database of constructive and decorative elements of blouses of this period. The analytical-typological, comparative-typological method, as well as the method of structuring illustrative materials - photographs, drawings from fashion magazines, advertising posters has been used. Results. A historical analysis of models of women’s blouses 50-60-ies of the twentieth century was conducted. taking into account the influence of social and cultural events of that time. More than 200 images of women’s blouses that were fashionable and relevant during the period in France, England, Canada and the United States were analyzed. The basic artistic-compositional characteristics of blouses and general tendencies of their shape, silhouette, cut, constructive and decorative elements, color scale are determined. Also, a database of constructive and decorative elements for the design of women’s clothing collections in costume stylistics of those years has been developed. The scientific novelty consists in systematization of artistic compositional signs of women’s blouses of the 1950s-1960s and the development of a database of constructive and decorative elements for their further use in the design process of an industrial collection of modern women’s clothing. Practical significance. The basic artistic-compositional and constructive-decorative features of the device of women’s blouses of the 1950s-1960s were determined, a database of basic structural and decorative elements for the design of collections of clothing models was developed.